Fiscal Ratios and Macroeconomic Performance under Fiscal Governance in Indonesia - Irfan Maulana (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2026)
This study examines the relationship between fiscal ratios and short-run economic performance in Indonesia. Rather than treating economic governance as an abstract institutional construct, the analysis positions fiscal ratios as indicators of fiscal governance capacity and evaluates their association with observable macroeconomic outcomes. Using annual data, the study focuses on how revenue effectiveness, expenditure efficiency, and fiscal balance relate to variations in economic growth. The empirical analysis employs time-series regression with Newey–West standard errors to address potential autocorrelation and heteroskedasticity. To strengthen the robustness of the findings, alternative model specifications incorporating dynamic elements are also estimated. The results indicate that selected fiscal ratios exhibit statistically meaningful associations with economic growth, although the direction and magnitude of the effects vary across specifications. In particular, expenditure-related indicators tend to show a more consistent relationship with growth performance than revenue-side measures. These findings suggest that fiscal governance mechanisms may influence economic outcomes through indirect and short-term channels rather than immediate growth acceleration. Given the limited time horizon of the data, the results should be interpreted with caution. Nevertheless, the study contributes to the empirical literature by highlighting how fiscal governance capacity, as reflected in fiscal ratios, is linked to short-run macroeconomic performance in a developing country context.